Advancing gastrointestinal nematode treatment through phytochemicals administration to lambs - Miró, María Victoria (2023)
In the last 50 years, few antiparasitic drugs with new mechanisms of action have been introduced; leading to a global increase of drug resistance. Therefore, the search for alternative pharmacological tools is a priority in ruminant production systems. While numerous phytochemicals demonstrated efficacy against parasites in vitro, the transition to in vivo characterization poses a growing challenge. The drug concentration attained in the target parasites and, the resulting pharmacological effect are directly influenced by the administration route and pharmaceutical formulation. The aim of the current work was to analyze the pharmacokinetic-pharmacodynamic relationship of the combined administration of carvone (CNE) and ivermectin (IVM) to lambs. Three trials were conducted to evaluate the pharmacological interaction between CNE and IVM in lambs infected with nematodes. Drug concentrations were measured in plasma, target tissues and H. contortus by HPLC with fluorescent (IVM) and ultraviolet (CNE) detection. The decrease in fecal egg count was used as an indicator for estimating the efficacy of both compounds. CNE significantly enhanced the plasma bioavailability of IVM. CNE showed a moderate anthelmintic effect, which was greater on the susceptible isolate of H. contortus. After the combination of CNE and IVM as an oral emulsion, both compounds were quantified in H. contortus recovered from infected lambs. Although the coadministration of CNE and IVM in lambs demonstrated a moderate in vivo anthelmintic effect and enhanced systemic availability of IVM, the concentrations achieved in both target tissues and parasites remained notably lower compared to those documented to induce anthelmintic effects in the in vitro assays. Consequently, these levels were insufficient to achieve the desired optimal efficacy. Innovative pharmaceutical formulations are required to establish phytochemicals as a useful pharmacological tool for controlling nematodes in ruminants.